CRITERIA, INDICATORS AND LAWS OF SMALL BUSINESS DEVELOPMENT - Israilov, Rusrambek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the main criteria, indicators and laws of small business development are analyzed in detail. Small businesses play an important role in the economy, supporting innovation, creating jobs and contributing to economic stability. The article analyzes the factors affecting the development of small business, the indicators used to measure this development, and the laws of development. The research results serve to develop effective management strategies for small business entities.